Intercomparison of a portable and two stationary mobility particle sizers for nanoscale aerosol measurements. Issue 7 (2nd July 2016) - Fonseca, A. S.; Viana, M.; Pérez, N.; Alastuey, A.; Querol, X.; Kaminski, H.; Todea, A. M.; Monz, C.; Asbach, C.
ABSTRACT: During occupational exposure studies, the use of conventional scanning mobility particle sizers (SMPS) provides high quality data but may convey transport and application limitations. New instruments aiming to overcome these limitations are being currently developed. The purpose of the present study was to compare the performance of the novel portable NanoScan SMPS TSI 3910 with that of two stationary SMPS instruments and one ultrafine condensation particle counter (UCPC) in a controlled atmosphere and for different particle types and concentrations. The results show that NanoScan tends to overestimate particle number concentrations with regard to the UCPC, particularly for agglomerated particles (ZnO, spark generated soot and diesel soot particles) with relative differences >20%. The best agreements between the internal reference values and measured number concentrations were obtained when measuring compact and spherical particles (NaCl and DEHS particles). With regard to particle diameter (modal size), results from NanoScan were comparable < [± 20%] to those measured by SMPSs for most of the aerosols measured. The findings of this study show that mobility particle sizers using unipolar and bipolar charging may be affected differently by particle size, morphologies, particle composition and concentration. While the sizing accuracy of the NanoScan SMPS was mostly within ±25%, it may miscount total particle number concentration by more than 50% (especially for agglomerated particles), thus making it unsuitable for occupational exposure assessments where high degree of accuracy is required (e.g., in tier 3). However, can be a useful instrument to obtain an estimate of the aerosol size distribution in indoor and workplace air, e.g., in tier 2. Published with liscence by American Assotiation for Aerosol Research